2018
DOI: 10.1177/1756284818765920
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to colonoscopy at 1 year following resection of localized colon cancer: a retrospective cohort study

Abstract: Background: For patients with stages I-III colon cancer who have undergone surgical resection, guidelines recommend surveillance colonoscopy at 1 year. However, limited data exist on adherence and associated factors. We aimed to determine the rate of adherence to surveillance colonoscopy at 1 year among nonmetastatic colon cancer patients who underwent resection and factors associated with adherence. Methods: In this population-based retrospective cohort study, the Surveillance, Epidemiology, and End Results (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 47 publications
1
7
1
Order By: Relevance
“…Blacks had lower receipt of surveillance colonoscopy than NHWs, and this may contribute to the poorer CRC survival among Black patients 12,19 . Other studies with larger samples of minorities have suggested that Hispanics are less likely to receive surveillance; however, we found no statistically significant difference between Hispanics and NHWs 20 …”
Section: Discussioncontrasting
confidence: 74%
See 1 more Smart Citation
“…Blacks had lower receipt of surveillance colonoscopy than NHWs, and this may contribute to the poorer CRC survival among Black patients 12,19 . Other studies with larger samples of minorities have suggested that Hispanics are less likely to receive surveillance; however, we found no statistically significant difference between Hispanics and NHWs 20 …”
Section: Discussioncontrasting
confidence: 74%
“…Neighborhood socioeconomic determinants contribute to racial/ethnic disparities in receipt of cancer‐related outcomes 12,20 . A key finding was that Hispanics residing in neighborhoods with an MHI of ≥$90,001 had significantly lower odds of surveillance colonoscopy than Hispanics residing in neighborhoods with lower MHIs.…”
Section: Discussionmentioning
confidence: 99%
“…Research studies have highlighted that individuals from medically underserved populations are less likely to receive counseling to complete screening, 23 have less access to preventive care and CRC treatment after diagnosis, 24 are less likely to complete diagnostic colonoscopy after abnormal FIT, 20 and are also less likely to receive colonoscopy surveillance after curative CRC treatment. 25 26 Given the impact of COVID-19 on our research activities, we propose the following solutions for individuals facing similar challenges ( Table 1 ).…”
Section: Crc Research In the Underservedmentioning
confidence: 99%
“…26,27 Various studies have shown that sex, age, length of hospital stay, histopathological grading and stages of cancer, number of medications, co-morbidity, and complications are determinants of DRP development. 22,24,28,29 A comprehensive study of DRPs would provide valuable insight for healthcare providers to reduce the incidence of DRPs and improve treatment outcomes in cancer patients. 30 DRPs can be prevented and managed with clinical pharmacists.…”
Section: Introductionmentioning
confidence: 99%